International organizations and the implementation of the responsibility to protect the humanitarian crisis in Syria - Silander, Daniel; Wallace, Don (Global politics and the responsibility to protect, 2015)
This book seeks to understand the obligation of the international community to implement the principles of the Responsibility to Protect (R2P).With a focus on the humanitarian crisis in Syria, the volume examines what formal responsibility and actual capability international institutions have to protect and prevent civilians from systematic mass atrocities and presents an analysis of several prominent international organizations (IOs). Each chapter focuses on a specific organization and explores their formal responsibilities and how these pertain to the obligations of the R2P. Existing capabil.